Not Just Bystanders: A Qualitative Study on the Vicarious Effects of Surgical Training on the Wellness of Support Persons for Trainees. Issue 3 (September 2021) - Evans, Julie; Kemp, Michael T.; Rivard, Samantha J.; Sharma, Sriganesh B.; Williams, Aaron M.; Coleman, Dawn; Dimick, Justin; Sandhu, Gurjit
Abstract : Objective: To obtain insights into the effects of surgical training on the well-being of support persons. Summary Background Data: Surgical trainee wellness is a critical priority among surgical educators and leaders. The impact of surgical training on the wellness of loved ones who support trainees has not been previously studied. Methods: This qualitative study employs semi-structured interviews of 32 support persons of surgical trainees at a single tertiary care center with multiple surgical specialty training programs. Interviews focused on perceptions about supporting a surgical trainee. Transcripts underwent thematic analysis with semantic and conceptual coding. Key themes regarding the effects that caring for a trainee has on support persons are reported. Results: Three key themes were identified: (1) Sacrifices—support persons report significant tangible and intangible sacrifices, (2) Delaying life—life is placed on hold to prioritize training, and (3) A disconnect—there is a disconnect and a lack of recognition of support person needs that require greater awareness and targeted interventions. Conclusions: The impact of surgical training can extend beyond trainees and can affect the wellness of their support persons who endure the effects of training alongside trainees. Programs should be aware of these effects and develop meaningful strategies to aid trainees and their support persons. Abstract : Supplemental Digital Content is available in the text